Muscle relaxation enhances motor imagery capacity in people with anxiety: A randomized clinical trial - Sara Trapero-Asenjo; Sara Fernández-Guinea; Aymeric Guillot; Daniel Pecos-Martin; Susana Nunez-Nagy (PLoS ONE, 2025)
Background Motor imagery is the mental representation of a movement without physical execution. When motor imagery is performed to enhance motor learning and performance, participants must reach a temporal congruence between the imagined and actual movement execution. Identifying factors that can influence this capacity could enhance the effectiveness of motor imagery programs. Anxiety frequently occurs in sports and rehabilitation where motor imagery is a relevant technique. It is associated with increased muscle tension and impairs the memory processes involved in motor imagery. This study aimed to determine whether muscle relaxation before motor imagery practice can influence motor imagery capacity and temporal congruence in anxious individuals, during internal and external visual imagery, and kinesthetic imagery. Methods A randomized clinical trial was conducted in 55 young adults (20.3±2.8 years; 40 females; 15 males) with anxiety (percentile ≥75% on the State-Trait Anxiety Inventory). 26 participants were assigned to the relaxation group and 29 to the control group through stratified randomization. Motor imagery capacity and temporal congruence were assessed using the Movement Imagery Questionnaire-3 at 2 points (t1 and t2). Between t1 and t2, participants in the relaxation group underwent abbreviated progressive relaxation training. Electrodermal activity and heart rate variability were recorded to evaluate the relaxation effect. Results Data revealed a significant improvement in motor imagery capacity in the relaxation group, while the temporal congruence was not impaired in both groups. Conclusion Pre-motor imagery muscle relaxation might improve motor imagery capacity in anxious individuals. This finding may contribute to better tailor motor imagery programs and to adjust motor imagery guidelines and recommendations for people with anxiety. This study has been registered in ClinicalTrials.gov (NCT04973956).